Transformasi Digital Pembelajaran: Pengenalan Teknologi Generative Voice Artificial Intelligence di Sekolah Dasar Kabupaten Malang - Rizkiana Maharddhika; Mushoffan Prasetianto; Mumtaza Nurul Maulana (Jurnal Pemberdayaan Masyarakat, 2026)
The growth of Artificial Intelligence (AI) technology has had a significant impact on various aspects of life, including education. ElevenLabs Generative Voice AI is an AI technology capable of generating high-quality synthetic speech from written text, which especially can be used for auditory learning materials in schools. Hence, this community service aims to introduce the use of ElevenLabs technology as a tool for creating innovative media for elementary school teachers. Approximately twelve (12) teachers at SDN Pucangsongo, Malang regency, participated in a training program that allowed them to learn how to create AI-based educational media. Evaluation results also showed that the teacher's ability to understand how to create learning media using ElevenLabs improved significantly. The average evaluation score rose from 63.9 – 80, and most participants showed positive attitude towards the training program. Through this activity, the teachers now recognize that generative voice AI technology can offer a practical solution to address the limited audio resources in elementary schools.